Afterword: An exhibition about hospitality. A more sensitive perception of vulnerability. Issue 1 (1st April 2021) - Brugère, Fabienne
This afterword reflects on the tension between art, politics and philosophy at the thematic core of this Special Issue, 'Migrants and Refugees Between Aesthetics and Politics'. Brugère calls attention to a recent art exhibition ‐ one that came out of her book with Guillaume Le Blanc, The End of Hospitality ‐ at the Museum of the History of Immigration, in Paris, as a way to frame a conflict between two ideas of hospitality, or the broad ethical gesture to welcome others and the political right that more and more governments are unable to uphold as borders tighten around the globe. The afterword elaborates on the aims of the exhibition, namely, to show 'a correspondence between art and philosophy on the question of hospitality'. Rather than a mere representation of discourse around migration, the artwork displays a praxis of the imagination, one in which cultural production by and about refugees brings spectators to recognize a shared sense of vulnerability and to question received ideas on migration. In this manner, contemporary art forms become an essential link in the ongoing struggle between ethics and politics.